The Effect Analysis of Organizational Citizenship Behavior on Employee Performance - Dewani, Shinta Laura; Swatantra, Gallant Yosava (Indonesian Journal Publisher, 2024)
The behavior expected by companies today extends beyond in-role behavior (according to job descriptions) to include extra-role behavior. The behaviors described above, exceeding the prescribed role descriptions within a company, are referred to as Organizational Citizenship Behavior or OCB. This research aims to investigate the influence of OCB dimensions, consisting of altruism, conscientiousness, civic virtue, courtesy, and sportsmanship, on employee performance, so that we can make sure is it really important to be a super loyal employee who works extra miles to the company, or it actually has nothing to do with the performance and only burdens employees without adding self-value. This research employs a quantitative approach with the primary data collection method being a Likert scale questionnaire, with employee performance as the dependent variable and 5 dimensions of Organizational Citizenship Behavior (OCB) as independent variables. The results indicate that all independent variables of OCB have a significant positive impact on employee performance, except for Conscientiousness, which does not influence employee performance. The overall illustration of the research findings suggests that when employees exhibit OCB or behavior that is willing to exert extra effort beyond the job description, their performance will also improve. This indicates that the positive contributions made by employees beyond their direct responsibilities can contribute to an overall performance enhancement.